Groundwater quality in Ponjong Karst, Gunungkidul Regency, Special Region of Yogyakarta - Avellyn Shintya Sari; Sari Bahagiarti K; Suharsono Suharsono; C Prasetyadi (Lembaga Penelititan dan Pengabdian kepada Masyarakat - Institut Teknologi Adhi Tama Suraba, 2020)
The hydrogeological condition of a region is determined by the type of lithology, morphology, and subsurface conditions where the condition is very helpful in the study of groundwater exploration. Especially when we encounter interesting geological conditions when the groundwater exploration in the karst area in which volcanic rocks are resulting from the activities of the active volcano in the past. Groundwater exploration at Ponjong area and surrounding does have its special characteristics, because it has 2 different rock characteristics where the northern part of the research area in the form of a karst area (limestone of Wonosari Formation) while the southern part is an area of ancient volcanoes with dominant volcanic rocks from Wuni Formation, As for the research on the above and subsurface research area where the research is conducted based on surface geology mapping, geoelectric data collection, and groundwater sampling. Geological mapping includes geomorphological data, stratigraphy, and geological structure. The aquifer system of the research area can be divided into two systems, inter-grain aquifer systems, and fracture aquifer systems. Overall quality groundwater in the research area is quite good. Ponjong District there are mining activities that have resulted in changes in the land use system in the area. This can cause changes in the water surplus in the area due to the changing catchment area.